China's Collective Forest Tenure Reform and the Future of the Giant Panda. Issue 4 (16th November 2014) - Yang, Biao; Busch, Jonah; Zhang, Li; Ran, Jianghong; Gu, Xiaodong; Zhang, Wen; Du, Beibei; Xu, Yu; Mittermeier, Russell A.
Abstract China has recently reformed its system of collective forest tenure to allow commercial logging, increased collection of firewood and nontimber forest products by outside enterprises, unmanaged tourism, and certain types of industrial development to occur in collective forests where these activities were previously restrained. The reform would also allow private or public agencies to buy back certain development rights from communities for conservation purposes ("eco‐compensation"). We examine the impacts that the tenure reform could have on the survival of the giant panda, with or without eco‐compensation in place. We estimate that 1, 229 million in effective eco‐compensation payments could prevent an estimated 15% decline in the giant panda population, whereas an additional 3, 707 million for effective eco‐compensation and restoration of potential habitat could restore the giant panda population to an estimated 40% above current levels. Specifically, we identify 14 key areas that link fragmented panda populations and habitats, and where approximately 779 million is needed for eco‐compensation, matched with an additional investment of 131 million for the restoration of native forest habitat.